A practical method for lingual retainer fixation before direct bonding: Clinical suggest - Tondelli, Pedro Marcelo [UNESP]; Mendonça, Marcos Rogério de [UNESP]; Cuoghi, Osmar Aparecido [UNESP]; Pereira, Alex Luiz Pozzobon [UNESP]; Busato, Mauro Carlos Agner [UNESP] (Taylor & Francis, 2009)
The retention phase is initiated after orthodontic treatment completion to prevent orthodontic relapse. There are several techniques, direct and indirect, available for placing bonded lingual retainers, but none of them is considered as a standard clinical protocol. The best choice should be the association of simplicity and efficiency. This article presents a practical method sequence for fixation of the lingual retainer before direct bonding. © 2009 Elsevier Ltd and the Japanese Orthodontic Society.
Keywords: Composite resin; Lingual retainer; Orthodontics